2018
DOI: 10.20471/acc.2018.57.02.05
|View full text |Cite
|
Sign up to set email alerts
|

Patient, Healthcare System and Total Delay in Tuberculosis Diagnosis and Treatment among Serbian Population

Abstract: SUMMARY – Currently, topical are studies that examine different reasons for delay of tuberculosis (TB) diagnosis and its impact on disease prognosis. The aim was to examine three time periods associated with treatment delay: patient related, health system related and total delay. This retrospective-prospective study included 100 consecutive patients hospitalized at Department of Pulmonology, Clinical Center of Serbia, in the period from March to December 2015. Study results showed median patient delay to be 92… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Thus, in current smokers, the diagnosis delay was shorter (median = 19 days) than in non-smokers (median = 26 days). In a study conducted in Serbia, a medium, positive, and statistically significant correlation was found between the number of cigarette smoked and the patient delay [27].…”
Section: Discussionmentioning
confidence: 96%
“…Thus, in current smokers, the diagnosis delay was shorter (median = 19 days) than in non-smokers (median = 26 days). In a study conducted in Serbia, a medium, positive, and statistically significant correlation was found between the number of cigarette smoked and the patient delay [27].…”
Section: Discussionmentioning
confidence: 96%
“…Alcohol abuse and unemployment presented an association with longer delays, more specifically between beginning of symptoms and seeking help from the healthcare services. Previous studies [ 23 , 50 , 51 ] have established that patients with addictions are less likely to visit the healthcare services in a timely manner. This may result from the fact that patients who consume alcohol in excess may not seek, or easily have access to, healthcare providers when they start presenting symptoms and realize they are ill, resulting in delayed diagnosis and more advanced disease [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Delays in any part of the healthcare-seeking process for patients with tuberculosis can lead to the transmission of Mycobacterium tuberculosis, and are one of the major factors hindering the achievement of the 2030 tuberculosis elimination goal. [1,2] Patient delay (onset of symptoms to first visit) may increase the severity of the disease, prolong patient suffering, lead to complications, affect treatment outcomes and exacerbate the financial burden on patients, [3,4] and on the other hand, may increase the risk of tuberculosis infection in the population, leading to higher morbidity and mortality. [5] Minimizing the delays that may occur in patients with tuberculosis is a key part of the tuberculosis control chain.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of region of residence, some studies [3,14] have shown that patients living in less economically developed areas (rural or peri-urban) are more likely to experience patient delay, which may be related to the lack of transportation and single mode of travel in rural areas, the relative scarcity of healthcare resources, and the poorer accessibility to healthcare.…”
Section: Introductionmentioning
confidence: 99%